TINJAUAN YURIDIS HAK-HAK NASABAH PEGADAIAN DALAM HAL TERJADI PELELANGAN TERHADAP BARANG JAMINAN - Ronny Siantury Irawan (Universitas 17 Agustus 1945 Samarinda, 2021)
ABSTRACTIn a pledge agreement that has been agreed to be carried out by the parties, where the agreement creates rights and obligations that must be fulfilled by the parties. If an achievement is not fulfilled, it will cause consequences that must be held accountable for the act and require the parties to compensate for the loss. This study aims to find out about the implementation of the pawn agreement between PT. Pegadaian (Persero) and its customers in relation to the principle of freedom of contract, know the rights and obligations of PT. Pegadaian (Persero) and customers in the pawn agreement and know the legal consequences if one of the parties makes a mistake in the pawn agreement. The approach method used in this research is a normative method where the method that examines the law is based on the rules and principles in law.This writing uses a normative type of research, where the law is conceptualized as what is written in the legislation (law in books) or the law is conceptualized as a rule or norm which is a benchmark for human behavior that is considered appropriate.The results of this study indicate that the rights and obligations of the parties are implemented if PT. Pegadaian (Persero) and the debtor have agreed on an agreement and require the parties to implement it. If the debtor does not fulfill the obligation to pay off and redeem the pawned goods in accordance with Article 1243 of the Civil Code, the consequence is that the pawned goods will be auctioned. PT. Pegadaian (Persero) also has an obligation to look after and maintain the customer's pawned goods. If the pawned goods are damaged or lost, the act is considered an unlawful act in accordance with Article 1365 of the Civil Code due to errors and omissions resulting in the customer experiencing a loss and requiring PT. Pegadaian (Persero) to compensate for the loss. The legal terms of the agreement are stated in Article 1320 of the Civil Code. Given the importance of an agreement, so that problems do not arise in the future due to someone's lack of understanding in making an agreement, we will explain some of the requirements that must be met in order for the agreement to be valid and binding on the parties. Article 1320 of the Civil Code states that there are 4 (four) conditions for the validity of an agreement, namely the existence of an agreement for those who bind themselves; The ability of the parties to enter into an engagement; A certain thing; and a lawful cause. Keywords: Mortgage Agreement, Legal Responsibility, Valid Terms of Agreement